Management of thrombocytopenia - Izak, Marina (Faculty of 1000 Ltd, 2014)
Thrombocytopenia is one of the most common hematologic disorders, characterized by an abnormally low number of platelets from multiple causes. The normal count of thrombocytes (platelets) is between 150,000 and 450,000 per microliter. The clinical expression of thrombocytopenia has broad variation from asymptomatic to life-threatening bleeding. Various syndromes and diseases are associated with thrombocytopenia. Thrombocytopenia is sometimes a first sign of hematologic malignancies, infectious diseases, thrombotic microangiopathies, and autoimmune disorders, and is also a common side effect of many medications. There are more than 200 diseases that include low number of platelets among their symptoms. A brief discussion of the most common etiologies and management of them is provided in this review.